ChemInform Abstract: Titanocene(III)‐Catalyzed 6‐exo versus 7‐endo Cyclizations of Epoxypolyprenes: Efficient Control and Synthesis of Versatile Terpenic Building Blocks. Issue 16 (22nd April 2014) - Justicia, Jose; Jimenez, Tania; Miguel, Delia; Contreras‐Montoya, Rafael; Chahboun, Rachid; Alvarez‐Manzaneda, Enrique; Collado‐Sanz, Daniel; Cardenas, Diego J.; Cuerva, Juan M.
Abstract Additionally a computational study of the regioselectivity is presented.